Associated Factors for Dropout of First Vs Third Doses of Diphtheria Tetanus Pertussis (DPT) Vaccination in Nepal - Thapa, Kanchan (Adv Prev Med, 2021)
BACKGROUND: Immunization acts as a key intervention to reduce under-five mortality and morbidity. Despite global progress on vaccination, difficulties in the utilization of this service in developing countries have been observed. According to Nepal Demographic and Health Survey (NDHS) 2016, only 78% of children received a complete dose of vaccine among which the first-dose receiver of DPT is 98%, whereas only 83% received a third dose. This study aims to explore the influencing factors of DPT vaccination dropout in Nepal. METHODS: The explorative study was done through secondary data analysis of NDHS 2016. The KR file was used for the analysis of information for 2883 children. Factors influencing dropout of DPT vaccination were explored against the independent variables such as external environment, predisposing factors, and enabling resources. All the analyses were weighted before the analysis. The descriptive, bivariate, and multivariate analyses were performed. The variables showing collinearity have been removed in the final model. RESULTS: A higher dropout was reported in Terai (18.9%) and province 2 (22.0%), among uneducated mothers (18.1%) and uneducated fathers (19.4%), less than once a week internet users (22.2%), the nonradio listener (17.4%), who had <4 ANC visits (22.7%), home delivery (19.2%), no advised SBA (19.1%), long distance to health facility (17.9%), no iron supplementation in pregnancy (24.3%), and PNC by TBA/others (21.1%). All these tested relationships were found statistically significant (P value <0.05). The aOR for dropout was found to be 7.94 (4.07–15.51) for mothers with less than 4 or no ANC visit, long distance to health facility 4.68 (1.98–10.67), province 2 3.53 (1.13–11.03), and mother without formal employment 2.33 (1.52–3.55). CONCLUSION: Factors related to health services, distance, provinces, and socioeconomic status of the family were influencers for vaccine dropout. Targeted intervention towards disadvantaged regions, counseling the mother during ANC, improving the education status of parents, access to the health facility, and use of mass media for advocacy are hereby recommended.